2016
DOI: 10.3390/ijerph13050478
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Nitrogen Load Resulting from Biofuel Mandates

Abstract: The Energy Policy Act of 2005 and the Energy Independence and Security Act (EISA) of 2007 were enacted to reduce the U.S. dependency on foreign oil by increasing the use of biofuels. The increased demand for biofuels from corn and soybeans could result in an increase of nitrogen flux if not managed properly. The objectives of this study are to estimate nitrogen flux from energy crop production and to identify the catchment areas with high nitrogen flux. The results show that biofuel production can result in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Despite the ORB being an important basin for current and future biofuel feedstock productions, to date, limited studies explored the associated impacts on the basin water resources (Alshawaf et al ., ; Panagopoulos et al ., ). Alshawaf et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the ORB being an important basin for current and future biofuel feedstock productions, to date, limited studies explored the associated impacts on the basin water resources (Alshawaf et al ., ; Panagopoulos et al ., ). Alshawaf et al .…”
Section: Introductionmentioning
confidence: 99%
“…Alshawaf et al . () applied the SPARROW regression model for the entire Mississippi River basin to assess the land use needs and nitrogen flux to meet the 2022 biofuel target from increased production of hay, corn, and switchgrass. Panagopoulos et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, increased fuelrelated agricultural production also puts additional nutrientrelated stress on ecosystems. 12 The N impacts of food and biofuel systems have been studied separately, but the link between corn ethanol and animal food systems has not been considered in N studies. potential, energy, and water use impacts of corn ethanol are well-studied, 13−18 and researchers have found that consideration of ethanol coproducts has a significant impact on results and is essential to accurately estimate environmental impacts of corn ethanol production.…”
Section: Introductionmentioning
confidence: 99%